Comparative evaluation of Acheta domesticus and Hermetia illucens as alternative protein sources for the growth, health, and meat quality of the broiler - Mustafa, Farwa; Sajjad, Asif; Sajjad, Muhammad; Ali, Mudssar; Bashir, Hafiza Sehrish; Abbas, Muhammad Ghazanfar; Binyameen, Muhammad; Mozūratis, Raimondas (Frontiers in Animal Science, 2025)
IntroductionInsects are receiving increasing attention due to their potential to enhance farming efficiency and sustainability, mitigate vast quantities of bio-waste, and improve animal performance. It is hypothesized that replacing soybean meal with Acheta domesticus will improve broiler productive performance, health, and meat quality. Therefore, the objective of this study was to assess the effect of the gradual replacement of soybean meal (4%, 8%, and 12%) with house cricket (A. domesticus) and black soldier fly (Hermetia illucens) on productive performances, hematology, intestinal morphology, and meat quality attributes of male broiler (Ross 308). MethodsA total of 350 1-day-old chicks (39.23 ± 0.19 g) were divided into seven groups (five pens per group and 10 chicks per pen) following a completely randomized design. The seven groups included 4%, 8%, and 12% SBM replacements with A. domesticus and H. illucens. Soybean meal was the basal diet considered the control. ResultsThe broilers fed 12% A. domesticus, or 12% H. illucens had significantly higher ((p 0.05) live weight, average daily weight gain, and improved feed conversion ratio than the broilers fed basal (SBM) diet throughout starter, grower, and finisher phases. Hematology (complete blood count and serum biochemistry traits) and intestinal morphology (villus height, villus width, crypt depth, and villus height-to-crypt depth ratio) of the broilers improved when fed on 12% A. domesticus and 12% H. illucens meals as compared to the control group (p < 0.05). Feeding 12% A. domesticus and 12% H. illucens also had a significant positive impact on the meat quality traits of broilers, such as maximum redness (a*) and yellowness (b*) with minimal cooking loss and lightness (L*) (p < 0.05) than the broilers fed the control diet. DiscussionUsing insect meal as an alternative to traditional feed sources could contribute significantly to the sustainable expansion of the poultry industry.